Comprehensive Evaluation of Environmental Policy for Water Pollutants and Greenhouse Gases Reduction in Jiaxing city, China - Feng XU; Nan XIANG; Shanshan WANG; Yang LI; Takeshi MIZUNOYA; Yabar HELMUT (European Regional Science Association (ERSA), 2011)
Recently, various environmental problems have been generated with the rapid economic development in China. That's because China currently over-emphasized economic development beyond environmental issues; therefore, now it is important to enforce optimal environmental policies in order to achieve economic development as well as environmental improvement. In this study, we selected Jiaxing city as research area for that the environmental pollution problem has become prominent with economic high growth, and we constructed environmental system model and social economic model to establish the scenarios. Through computer simulation, we can evaluate the efficiency of the comprehensive environmental policies from both environmental preservation and social economic development aspects. While the social-economic model shows the socioeconomic activities which are vital events, fortune and service, such as production, finance and budget; the environmental system model shows the water pollutants and the greenhouse gas movement in the region. The dynamic optimization simulation is accomplished based on this environmental and socio-economic system model. In view of the restriction on water pollutants, greenhouse gas total exhausted amount, and economic activity in the catchment area, the simulation we practiced can provide concrete inner-generating optimal policies which can achieve the best economic and environment improvement with the consideration of policy, regional and timing choice in Jiaxing City, China.
Keywords: 330